Pengaruh Persepsi Teknologi dan Persepsi Risiko Terhadap Kepercayaan Pengguna M-banking BRI Konvensional (Studi Pada Mahasiswa FEB UM Metro) - Sani, Elvara Ich; Ratmono, Ratmono (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the effect of technology perceptions and risk perceptions on the trust of M-Banking users. This type of research is quantitative research with the data used is field data (field research). Data collection was obtained from the results of questionnaires to 85 students of the Department of Management, Faculty of Economics and Business, UM Metro, which were taken using the formula from Slovin. Research data analysis was carried out using quantitative data analysis by testing instrument requirements, requirements analysis and hypotheses. The results showed that the technology perception variable obtained a t-count value of 1.428 <t-table (0.165) and a significance value of 0.006 <0.05, then H1 was accepted, which means technology perception had a greater and more significant effect on user trust, while the risk perception variable obtained t-value of 1.328 <t-table (0.165) and a significance value of 0.009 <0.05, then H2 is accepted, which means that risk perception has a significant effect on user trust. So that technology perceptions and risk perceptions have a simultaneous effect on trust in the use of m-banking Keywords: Perception of Technology, Perception of Risk, User Trust.